Students’ Perceptions of the Digital Access Centres at the University of South Africa - Tefo, Regina Mosima; Pitsoane, Enid Manyaku (Research in Social Sciences and Technology, 2023)
This paper sought to investigate the accessibility of Digital Access Centres as a resource for Unisa Students needing to access services away from campus. The Digital Access Centres are available in open-distance e-learning institutions like Unisa in a quest to reach students. Unisa regional computer labs are always fully packed with students queuing to access the computers to access online platforms to write and submit assignments. Students are also expected to use Digital Access Centres to access support services instead of travelling long distances to regional offices or campuses. This study investigated UNISA students’ perceptions and knowledge of Digital Access Centres. A qualitative research methodology was used. Data was generated through semi-structured interviews with thirteen students. The sample was drawn from a population of students who visit computer labs at the Gauteng Regional Service Centre. The data collected revealed that students do not know about Digital Access Centres despite information being available on myUnisa and myChoice brochures. The findings also revealed that few students are accessing Digital Access Centres, and those who visited the centres, indicated that the centres are not fully operational and struggle with connectivity.